PENGARUH PENERAPAN TEKNIK SPOTLIGHT DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 22 PADANG TAHUN PELAJARAN 2013/2014 - Mulina, Mulina; Rismen, Sefna; Lovia, Lita (STKIP PGRI Sumbar, 2013)
This research is motivated by the lack of understanding of mathematical concepts class VIII SMPN 22 Padang 2013/2014 school year . This study aims to determine whether students understanding of mathematical concepts using techniques Spotlight accompanied quiz better than that using conventional learning and see how the development of students understanding of mathematical concepts by applying spotlight with a quiz on the class VIII SMPN 22 Padang . This type of research is the design of experimental studies Against Random Subjects . Instrument used was a quiz and test understanding of mathematical concepts in the form of essays with a reliability test r11 = 0.861 . The data analysis technique used is the one party t test with the help of MINITAB Software . Based on the average values obtained quizzes every meeting that the development of understanding of mathematical concepts SMP 22 eighth grade students has increased Padang . And test the hypotheses derived P-value = 0.024 < Î± = 0.05 , then the hypothesis in this study received the students understanding of mathematical concepts using techniques Spotlight accompanied quiz better than students understanding of mathematical concepts using conventional learning in class VIII SMPN 22 Padang 2013/2014 Academic Year .